Optimalisasi Pembelajaran Pendidikan Pancasila dengan Mengintegrasikan Problem Based Learning (PBL) dan Kahoot dalam Model Pembelajaran Kolaboratif - Rina Endang Sulistiowati; I Wayan Widana (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This research discusses the optimization of implementing collaborative learning in the topic of norms and rules, integrating the Problem Based Learning (PBL) approach and Kahoot games with with assessments conducted both in groups and individually, along with observations by an observer. The study was conducted at MIN 1 Balikpapan with 28 students consisting of 12 male students and 16 female students. The assessment was designed to enhance students’ conceptual understanding and social skills through innovative and interactive methods. Observation results show that students are able to communicate and work together effectively in groups, while the presentation and question and answer stages encourage critical thinking skills and self-confidence. The group-based Kahoot game created a fun and competitive atmosphere, increasing students’ motivation and engagement in learning. Individual evaluations conducted at the end of the assessment measured the extent of students' understanding after the collaborative learning process. Overall, this assessment approach successfully fostered an active learning environment that supported the development of students' understanding of the material, social skills, and independent learning abilities. Final results showed that 29% of students achieved a perfect score of 100, 32% scored 90, 21% scored 80, and 14% achieved a passing grade with a score of 70. Only 4% of students did not meet the passing criteria, scoring 60. These findings demonstrate that the majority of students were able to achieve satisfactory learning outcomes.